The biology of terrestrial molluscs - Barker, G. M. (CABI, 2001)
This book presents a synthesis of current knowledge and research on the biology of terrestrial gastropod molluscs, which are of importance to human societies as food, medicine, crop pests, vectors of parasites, and as tools, personal ornamentation and currency in trade. It covers the morphology, phylogeny and systematics, structure and function of the various organ systems, feeding behaviour, life history strategies, behavioural ecology, population and conservation genetics, and soil biology and ecotoxicology of the terrestrial molluscs.